Deictic imaginings: semiosis at work and at play - West, Donna E. (Studies in Applied Philosophy, Epistemology and Rational Ethics, 2014)
This work represents the first integrated account of how deixis operates to facilitate points of view, providing the raw material for reconciling index and object. The book offers a fresh, applied philosophical approach using original empirical evidence to show that deictic demonstratives hasten the recognition of core representational constructs.  It presents a case where the comprehension of shifting points of view by means of deixis is paramount to a theory of mind and to a worldview that incorporates human components of discovering and extending spatial knowledge.  The book supports Peirce's triadic sign theory as a more adequate explanatory account compared with those of Bühler and Piaget.  Peirce's unitary approach underscores the artificiality of constructing a worldview driven by logical reasoning alone; it highlights the importance of self-regulation and the appreciation of otherness within a sociocultural milieu. Integral to this semiotic perspective is imagination as a primary tool for situating the self in constructed realities, thus infusing reality with new possibilities. Imagination is likewise necessary to establish postures of mind for the self and others. Within these imaginative scenarios (consisting of overt, and then covert self dialogue) children construct their own worldviews, through linguistic role-taking, as they legitimize conflicting viewpoints within imagined spatial frameworks.